Mariposas para los muertos - Liang, Diane Wei, 1966- (Nuevos tiempos (Madrid, Spain), 2011)
When Mei receives a call from the chief executive at Guanghua Record Company, she learns that one of Mr. Peng's top starlets--the beautiful pop star and troubled, mysterious Kaili--has been missing for four days. Mei must find the starlet while keeping up the record company's facade that nothing is amiss.